Empowering Women Farmers in Achieving Independence at TPK Citere KPBS Pangalengan - Putri, Fadisty Ailsa; Sulistyati, Marina; Nurlina, Lilis (Borong Newinera Publisher, 2024)
This research was conducted at TPK Citere, Sukamanah Village, Pangalengan District, Bandung Regency, during January - February 2024. The aim of the research was to examine the implementation of empowerment, level of independence, and empowerment in achieving independence of women farmers at TPK Citere KPBS Pangalengan. This research used a case study method with a qualitative approach. The variables observed included the empowerment of female farmers, covering cognitive, affective, and psychomotor aspects. Other variables observed were the independence of female farmers, including decision-making, creativity, and problem-solving skills. Informants were purposively selected, consisting of the extension worker coordinator, extension agents in the TPK Citere working area, and female farmers. The results of this research indicate that the empowerment carried out by KPBS Pangalengan is quite good. This is evidenced by the good cognitive and affective aspects possessed by female farmers, except for the psychomotor aspect. The independence of female farmers in TPK Citere is quite good, indicating potential independence because of their ability to make decisions, think creatively, and solve problems related to the material provided in the empowerment program by KPBS Pangalengan. Empowerment of female farmers sufficiently supports achieving independence as it can influence the mindset of female farmers in achieving independence in their farming business. With empowerment, female farmers can continue their efforts by utilizing all the abilities they have to continue experiencing development.